Melampaui Batas Cahaya: Kajian Tentang Fotosintesis Tumbuhan dalam Tafsir Bil Ilmi - Rosadi, Nora Juwita D.; Hakim, Lukman Nul (CV. ITTC INDONESIA, 2023)
This article explores the harmonious marriage between modern science and Quranic insights in the understanding of plant photosynthesis. Titled